Australia : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2005 Article IV Consultation highlights that Australia has implemented wide-ranging structural reforms and strengthened the frameworks for monetary and fiscal policies over the past two decades. As a result, Australia's economic expansion is now in its 14th year, with growth averaging 3 3/4 percent owing to a combination of strong job creation and high productivity growth. Growth is expected to rise from 2 1/4 percent in 2005 to about 3 1/2 percent in the medium term, although this will require continued strong growth in productivity.